Modal analysis of bioepoxy resin/fi que fi ber composite modal analysys (2018)
In this work, a modal analysis was applied on a bioepoxy/ fi ber composite material using the simulation (Finite Elements), experimentation and analytical modeling knowing the deviation between each of the methods of the solution. The material was elaborated using a bioepoxy resin and fi que fi bers in the distribution of weave under the technique of manufacturing the infusion vacuum. Tensile tests were performed on the composite material according to ASTM D3039 / D3039M to obtain the mechanical properties that allow the development of the mathematical model and the simulation and analysis of scanning electron microscopy to observe the adhesion between the fi ber and the matrix. The experimental modal analysis was performed by measuring the frequency response (FRF) under ISO 7626-2. The Euler-Bernoulli equation was used for analytical modeling, while the ANSYS fi nite element software was used for the simulation. It concludes that for the fi rst modes of material vibration obtained results close between the three methods, however for the third mode the error increases by the interaction between the matrix and the fi ber and the eff ects of the rotation of the cross-section of the test item.